2022
DOI: 10.5853/jos.2021.02831
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia: A Neglected Risk Factor for Ischemic Stroke?

Abstract: Hypertriglyceridemia is caused by defects in triglyceride metabolism and generally manifests as abnormally high plasma triglyceride levels. Although the role of hypertriglyceridemia may not draw as much attention as that of plasma cholesterol in stroke, plasma triglycerides, especially nonfasting triglycerides, are thought to be correlated with the risk of ischemic stroke. Hypertriglyceridemia may increase the risk of ischemic stroke by promoting atherosclerosis and thrombosis and increasing blood viscosity. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 146 publications
1
13
0
Order By: Relevance
“…We think hypertriglyceridemia may increase the risk of postoperative stroke by promoting atherosclerosis in the older patients ( Peng et al, 2017 ). Firstly, hypertriglyceridemia may theoretically cause subendothelial retention of remnant particles and elicitation of endothelial dysfunction, to establish chronic inflammation in the cerevascular ( Liang et al, 2022 ). Secondly, hypertriglyceridemia may cause hyperviscosity and promote thrombosis through a procoagulant effect involved in the disturbance of both blood coagulation and fibrinolysis, and led to postoperative stroke.…”
Section: Discussionmentioning
confidence: 99%
“…We think hypertriglyceridemia may increase the risk of postoperative stroke by promoting atherosclerosis in the older patients ( Peng et al, 2017 ). Firstly, hypertriglyceridemia may theoretically cause subendothelial retention of remnant particles and elicitation of endothelial dysfunction, to establish chronic inflammation in the cerevascular ( Liang et al, 2022 ). Secondly, hypertriglyceridemia may cause hyperviscosity and promote thrombosis through a procoagulant effect involved in the disturbance of both blood coagulation and fibrinolysis, and led to postoperative stroke.…”
Section: Discussionmentioning
confidence: 99%
“…102,103,106 The high seTG increases blood viscosity, reduces tissue microcirculation, and leads to brain or cardiovascular system ischemia. 107,108 Furthermore, hyperviscosity can cause pancreatic ischemia leading to cellular acidosis. 109 The acidosis may increase the potential for trypsinogen activation by cathepsin B 109 and initiate or aggravate inflammation.…”
Section: Induces or Aggravates Apmentioning
confidence: 99%
“…Another theory regarding the mechanism of HTG, which increases disease severity, focuses on plasma hyperviscosity (Figure 2). 102,103,106 The high seTG increases blood viscosity, reduces tissue microcirculation, and leads to brain or cardiovascular system ischemia 107,108 . Furthermore, hyperviscosity can cause pancreatic ischemia leading to cellular acidosis 109 .…”
Section: Mechanisms On How Htg Induces or Aggravates Apmentioning
confidence: 99%
“…Epidemiological data support associations of TG and low HDL with the development of cardiovascular diseases, and it was hypothesized that substantially increasing HDL or decreasing TG would lead to risk reductions ( Tall et al, 2022 ). However, the causal role was debated and clinical trials have shown discouraging results ( Tall, 2021 ; Liang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%